2013
DOI: 10.1371/journal.pone.0077300
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Potentiates TGFβ-Induction of Corneal Myofibroblast Development through an Oxidative Stress-Mediated p38-SMAD2 Signaling Loop

Abstract: Injuring mouse corneas with alkali causes myofibroblast expression leading to tissue opacification. However, in transient receptor potential vanilloid 1 channel (TRPV1-/-) knockout mice healing results in transparency restoration. Since TGFβ is the primary inducer of the myofibroblast phenotype, we examined the mechanism by which TRPV1 affects TGFβ-induced myofibroblast development. Experiments were performed in pig corneas and human corneal fibroblasts (HCFs). Immunohistochemical staining of α-smooth muscle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 38 publications
(51 reference statements)
3
43
0
Order By: Relevance
“…Specifically, it was shown that loss of p38 activity results in a decrease in phosphorylation of Smad2/3 after treatment with TGF-β39. This raises the possibility of cross-talk between p38 and Smad2/3 in post-translational regulation of Sox9.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it was shown that loss of p38 activity results in a decrease in phosphorylation of Smad2/3 after treatment with TGF-β39. This raises the possibility of cross-talk between p38 and Smad2/3 in post-translational regulation of Sox9.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts derived from TRPV1 knockout mice show impaired myofibroblast activation in culture (Okada et al, 2011). TRPV1 is also expressed in human stromal fibroblasts of the cornea where it enhances pro-fibrotic effects of TGF-β1 and promotes activation of Smad2 and mitogen-activated kinases (Yang et al, 2013a;Yang et al, 2013b). TRPV4 is a mechanosensitive channel and as such mediates substrate-stiffness induced myofibroblasts in liver and lung, and in M A N U S C R I P T…”
Section: Transient Receptor Potential Vanilloid (Trpv) Membrane Channmentioning
confidence: 99%
“…On the other hand, the inhibition of TRPV1 by CPZ impaired osteoblasts and osteoclasts differentiation (Idris et al, 2010), suggesting that TRPV1 signalling is important for the differentiation of these bone cell types. Moreover, TRPV1 activation is important for the TGF-␤1-induced formation of myofibroblasts from corneal fibroblasts (Yang et al, 2013). For a normal course of pregnancy, it is required a controlled hCTs differentiation and deregulations in this process are associated with gestational complications (Langbein et al, 2008;Lim et al, 1997;Ruebner et al, 2010).…”
Section: Figurementioning
confidence: 99%